A Cold War Odyssey - Nuechterlein, Donald E., 1925- (Book collections on Project MUSE., 2015)
The Cold War -- that long ideological conflict between the world's two superpowers -- had a profound effect not only on nations but on individuals, especially all those involved in setting and implementing the policies that shaped the struggle. Donald Nuechterlein was one such individual and this is his story. Although based in fact, the narrative reads like fiction, and it takes the reader behind the scenes as no purely factual telling of that complex story can. Presented as the story of David and Helen Bruening and their family, A Cold War Odyssey carries us across three continents. Against.